Pengaruh berbagai pengolahan kulit singkong terhadap kecernaan bahan kering dan bahan organik secara in vitro, protein kasar dan asam sianida (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The aims of the research was to evaluate the digestibility in vitro of dry matter and organic matter, the contents of protein crude and contents of HCN in cassava peel which were treated by fermentation, ammoniation, and fermentation ammoniation (amofer). Materials used in this research were cassava peel, EM4, urea, bran, HCL pepsin, rumen goat’s liqour and Mc Dougall butter solution. Oven, analytical balance, pH meter, glass beaker tube of CO2 gas, water bath, funnels, tube fermentor, centrifuges, ovens and thermos were used as the research equipment. This research consisted of 4 treatments and 4 replicators, (T0: Control; T1: Ammoniation; T2: Fermentation and T3: Ammonation Fermentation (Amofer). Data were analyzed using completely randomized design (CRD) and were continued by Duncan's Multiple Range Test (DMRT). The result of the research showed that dry matter content of T0, T1, T2 and T3 was 25.29, 50.69, 54.75 and 61.87% respectively. Organic matter digestibility contents of T0, T1, T2 and T3 was 23.52, 48.59, 2.62 and 61.87% respectively. Crude protein contents of T0, T1, T2 and T3 were 9.12, 22.28, 13.91 and 23,31% respectively. HCN content of T0, T1, T2 and T3 were 580.93, 3.10, 1.16 and 0.43 ppm respectively. The study showed that the treatment in T1, T2 and T3 had a significant effect (p>0.01) on dry matter and organic matter, crude protein and HCN. The conclusion of this research was that amofer treatment could increase dry matter and organic matter, crude protein and could reduce the levels of HCN in cassava peel. Keywords: cassava peel, ammoniation, fermentation and amofer